Elevated triglyceride-glucose index predicts mortality following endovascular abdominal aortic aneurysm repair - Li, Tan; Yang, Chao; Yang, Jun; Jing, Jingjing; Ma, Chunyan (Frontiers in Nutrition, 2023)
Abstract Background: Triglyceride-glucose (TyG) index has been increasingly studied as a simple and reliable predictor of adverse events of some cardiovascular disorders. However, its prognostic effect on postoperative outcomes in patients with abdominal aortic aneurysm (AAA) is still unknown. The current study aimed to explore the potential role of TyG index in predicting mortality of AAA patients following endovascular aneurysm repair (EVAR). Materials and methods: This retrospective cohort study analyzed the preoperative TyG index in a total of 188 AAA patients who underwent EVAR with the follow-up of 5 years. Data were analyzed with SPSS software Version 23.0. Association between the TyG index and all-cause mortality was evaluated using Cox regression models and Kaplan-Meier method. Results: Cox regression analyses showed that per 1-unit increment of TyG index was significantly associated with an increased risk of postoperative 30-day, 1-year, 3-year and 5-year mortality, even after adjustment for potential confounders (all P＜0.05). Kaplan-Meier analysis suggested that patients with high TyG index (≥8.68) had a worse overall survival (P=0.007). Conclusion: The elevated TyG index could be a promising predictive factor of postoperative mortality in AAA patients after EVAR.